Observational retrospective study of the association of initial healthcare provider for new-onset low back pain with early and long-term opioid use - Lewis E Kazis; Omid Ameli; James Rothendler; Brigid Garrity; Howard Cabral; Christine McDonough; Kathleen Carey; Michael Stein; Darshak Sanghavi; David Elton; Julie Fritz; Robert Saper (BMJ Open)
Objective This study examined the association of initial provider treatment with early and long-term opioid use in a national sample of patients with new-onset low back pain (LBP).Design A retrospective cohort study of patients with new-onset LBP from 2008 to 2013.Setting The study evaluated outpatient and inpatient claims from patient visits, pharmacy claims and inpatient and outpatient procedures with initial providers seen for new-onset LBP.Participants 216 504 individuals aged 18 years or older across the USA who were diagnosed with new-onset LBP and were opioid-naïve were included. Participants had commercial or Medicare Advantage insurance.Exposures The primary independent variable is type of initial healthcare provider including physicians and conservative therapists (physical therapists, chiropractors, acupuncturists).Main outcome measures Short-term opioid use (within 30 days of the index visit) following new LBP visit and long-term opioid use (starting within 60 days of the index date and either 120 or more days’ supply of opioids over 12 months, or 90 days or more supply of opioids and 10 or more opioid prescriptions over 12 months).Results Short-term use of opioids was 22%. Patients who received initial treatment from chiropractors or physical therapists had decreased odds of short-term and long-term opioid use compared with those who received initial treatment from primary care physicians (PCPs) (adjusted OR (AOR) (95% CI) 0.10 (0.09 to 0.10) and 0.15 (0.13 to 0.17), respectively). Compared with PCP visits, initial chiropractic and physical therapy also were associated with decreased odds of long-term opioid use in a propensity score matched sample (AOR (95% CI) 0.21 (0.16 to 0.27) and 0.29 (0.12 to 0.69), respectively).Conclusions Initial visits to chiropractors or physical therapists is associated with substantially decreased early and long-term use of opioids. Incentivising use of conservative therapists may be a strategy to reduce risks of early and long-term opioid use.